Strategi Pengembangan Kewirausahaan dan Dinamika Kompetitif Untuk Menciptakan Inovasi - Suci Indah Larassati; Fathir Naufal Ar Rizqi; Hesti Kusumaningrum (Pusat Riset dan Inovasi Nasional, 2024)
Entrepreneurship and innovation are two key elements in strengthening economic growth and creating added value across various industry sectors. This study aims to investigate the relationship between entrepreneurship development strategies and competitive dynamics in fostering innovation. The research methodology employed includes both qualitative and quantitative analyses of data from various industries and markets. Findings indicate that the use of targeted and adaptive entrepreneurship development strategies can enhance a company's competitive position in a volatile market. Additionally, healthy competitive dynamics and interactions among market players also play a crucial role in stimulating innovation through healthy competition and productive collaboration. The practical implications of this study highlight the importance for companies to develop entrepreneurial strategies that focus not only on creating economic value but also on generating social and environmental value. Moreover, collaboration between companies, governments, and educational institutions is necessary to create an ecosystem that supports sustainable innovation. This research contributes to understanding the complex dynamics between entrepreneurship, competition, and innovation in the rapidly changing global economy.